Women's mountaineering tourism: an empirical investigation of its theoretical constraint dimensions. Issue 4 (4th July 2018) - Doran, A.; Schofield, P.; Low, T.
Abstract: The purpose of this study is to investigate the perceived constraints on participating in mountaineering tourism faced by women, and to empirically verify the dimensionality of those constraints. Survey responses from 314 female mountaineers were collected and four constraint dimensions were identified using confirmatory factor analysis. Three of these dimensions: 'intra-personal', 'inter-personal' and 'structural' constraints support earlier findings in the extant literature, both in general and in the adventure literature more specifically. The identification of a fourth dimension relating to 'family' constraints represents a theoretical contribution to the literature and an additional barrier to women's participation in mountaineering tourism. In previous studies, 'family' constraints have typically been subsumed within 'inter-personal' or 'intra-personal' constraints, but have emerged as a distinctly separate constraint category for women in relation to this particular tourist activity. The findings also have important implications for adventure tourism management practice.